PERKEMBANGAN GERAKAN MAHASISWA ACEH DARI ORDE BARU HINGGA RFORMASI - Tia, Putri Adi (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2025)
This study examines the development of the student movement in Aceh from the New Order era to the Reformation era, focusing on the role and contributions of students in responding to social injustice, natural resource exploitation, and human rights violations, particularly in the Aceh region. This research employs a qualitative method with a historical approach to reconstruct the socio-political dynamics and patterns of student movements between 1966 and the early 2000s. Data were collected through literature review, archival documentation, and in-depth interviews with movement actors and historical witnesses. The findings reveal that, despite operating under political pressure and restricted space during the New Order regime, Acehnese students actively voiced structural and local issues and became key actors in overseeing the Reform era. During the Reformation period, the opening of democratic space allowed students to more freely organize protests, discussion forums, and solidarity networks. The student movement in Aceh has proven to be a significant socio-political force in advocating for justice, regional autonomy, and democratic transformation in Indonesia. Keywords: Student Movement, New Order, Reform Era, Social Injustice, Historical Approach, Regional Autonomy.